Impact of different ENSO positions and Indian Ocean Dipole events on Indonesian rainfall - Zaini, Ahmad Zul Amal; Vonnisa, Mutya; Marzuki, Marzuki (Vietnam Journal of Earth Sciences, 2024)
The El Niño Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) are widely recognized as the leading modes of climate variability in the tropics. This paper investigates the impact of different ENSO positions and IOD events on Indonesian rainfall during the period 1950–2021. The ENSO position is determined by the largest value of four Niño indices: Niño 1+2, Niño 3, Niño 3.4, and Niño 4. These ENSO positions are hereafter referred to as El-Niño/La-Niña 1+2, El-Niño/La-Niña 3, El-Niño/La-Niña 3.4, and El-Niño/La-Niña 4, respectively. The Dipole Mode Index (DMI) was used to observe IOD events. Different ENSO positions and IOD events result in different responses to Indonesian rainfall, obtained from the European Center for Medium-Range Weather Forecasts (ECMWF) ERA-5 data. The most significant decrease in rainfall occurs during the June-to-Septempber (JJAS) season of El-Niño 3. Conversely, during El-Niño 3.4, rainfall increases in the Sumatra and part of Kalimantan regions. The most significant increase in rainfall occurs during La-Niña 3.4, followed by La-Niña 4, La-Niña 3, and La-Niña 1+2. During a positive IOD phase, the southern part of western Indonesia experiences a decrease in precipitation of more than 30%. A more significant decrease in rainfall (>40%) occurs when a positive IOD co-occurs with El-Niño. During a negative IOD phase, Indonesia’s rainfall patterns become more spatially variable. An increase in rainfall is more pronounced when a negative IOD co-occurs with La-Niña. The difference in Indonesian rainfall during different ENSO positions and IOD phases is related to differences in atmosphere-ocean interaction during each condition.